2007
DOI: 10.1542/peds.2007-2329e
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Prevention of Childhood Obesity

Abstract: The majority of US youth are of healthy weight, but the majority of US adults are overweight or obese. Therefore, a major health challenge for most American children and adolescents is obesity prevention-today, and as they age into adulthood. In this report, we review the most recent evidence regarding many behavioral and practice interventions related to childhood obesity, and we present recommendations to health care providers. Because of the importance, we also suggest approaches that clinicians can use to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
324
1
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 376 publications
(345 citation statements)
references
References 247 publications
(281 reference statements)
4
324
1
10
Order By: Relevance
“…The prevention, assessment, and treatment reports provide detailed descriptions of studies for each topic. [1][2][3] …”
Section: Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevention, assessment, and treatment reports provide detailed descriptions of studies for each topic. [1][2][3] …”
Section: Causesmentioning
confidence: 99%
“…Their work is referred to throughout this report according to the area of review (prevention, assessment, or treatment), and their reports accompany this article. [1][2][3] Each multidisciplinary writing group reviewed the current literature to develop the recommendations. Because the science continues to lag behind the obesity epidemic, many gaps in evidence-based recommendations remain.…”
mentioning
confidence: 99%
“…Limiting SSB consumption has been acknowledged as one of the primary preventive strategies for combating the childhood obesity epidemic (5,6). The replacement of SSB for low energy alternatives such as water and diet beverages is likely to promote weight loss and facilitate obesity prevention (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies also found no association between fruit and vegetable intake and childhood adiposity [33][34][35] . Studies that found an inverse relationship between fruit or fruit and vegetable intake and adiposity tended to have a larger sample size, compared with those that found no association 36 . Although the findings available in the literature are still conflicting, it is important to highlight the crucial role of fruits and vegetables in health promotion.…”
Section: Discussionmentioning
confidence: 89%